The interpersonal communication process of social workers in fostering independence among the visually impaired: a case study of Panti Sosial Bina Netra (PSBN) Tuah Sakato Padang - Fatriana, Disya; Sarmiati, Sarmiati; Chatra, Emeraldy (Education and Social Sciences Review, 2025)
Visual impairment presents complex challenges in fostering independence, influenced by physical limitations, environmental barriers, and social perceptions. This study aims to analyze the process of interpersonal communication between social workers and visually impaired residents at Panti Sosial Bina Netra Tuah Sakato Padang in supporting their independence. Using a qualitative case study approach within a constructivist paradigm, data were collected through indepth interviews, participant observation, and documentation, with source and method triangulation applied to ensure validity. The findings reveal that the communication process develops gradually through four stages: introduction to establish a sense of safety, exploratory information exchange, emotional engagement through empathy and support, and the establishment of stable trust. These stages align with Altman and Taylor’s Social Penetration Theory and DeVito’s five dimensions of effective interpersonal communication: openness, empathy, positivity, respect, and equality. Consistent and adaptive communication was found to enhance the self confidence and motivation of visually impaired individuals in developing independent living skills. The results underscore interpersonal communication as a fundamental component in the success of social rehabilitation for people with visual disabilities.